Administering Windows server 2008 server core - Mueller, John, 1958- (Serious skills., 2008)
Intended for administrators, this guide includes a discussion of the interface, describes how to perform tasks that used to require the Windows GUI, and provides a reference for the relevant commands. It includes coverage of: useful maintenance; registry hacks; task automation; managing hardware; managing the network; and, working TCP/IP.